delta_theta =- (theta + sin(theta) - constant) / (1.0 + cos(theta))
1) delta_theta =delta_theta - (theta.....
or
delta_theta =-1*(theta+sin(......
delta_theta =- (theta + sin(theta) - constant) / (1.0 + cos(theta))
1) delta_theta =delta_theta - (theta.....
or
delta_theta =-1*(theta+sin(......
well you have =- so it would be:
delta_theta is assigned the value of the negative of ( theta + sin(theta) - constant) / (1.0 + cos(theta) )
if you had -= then it would be
delta_theta = delta_theta - (theta + sin(theta) - constant) / (1.0 + cos(theta))
Your book really should have covered all this
I am using msdn and vb6 and msdn does not in any sence of the word make much sence at all
MSDN is usually more of a reference. Better to find a good set of tutorials. I find the ones on this site adequate. You also may have made a typo. I don't see =- all the often, so maybe you meant -=, which has just the opposite meaning of +=.